Rapid improvement in severe long COVID following perispinal etanercept. (2nd December 2022) - Tobinick, Edward; Spengler, Robert N.; Ignatowski, Tracey A.; Wassel, Manar; Laborde, Samantha
Abstract: Background: This study aimed to describe the neurological improvements in a patient with severe long COVID brain dysfunction following perispinal etanercept administration. Perispinal administration of etanercept, a novel method designed to enhance its brain delivery via carriage in the cerebrospinal venous system, has previously been shown to reduce chronic neurological dysfunction after stroke. Etanercept is a recombinant biologic that is capable of ameliorating two components of neuroinflammation: microglial activation and the excess bioactivity of tumor necrosis factor (TNF), a proinflammatory cytokine that is a key neuromodulator in the brain. Optimal synaptic and brain network function require physiological levels of TNF. Neuroinflammation, including brain microglial activation and excess central TNF, can be a consequence of stroke or peripheral infection, including infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19. Methods: Standardized, validated measures, including the Montreal Cognitive Assessment, Beck Depression Index-II (BDI-II), Fatigue Assessment Scale, Controlled Oral Word Association Test, Trail Making Tests, Timed Finger-to-Nose Test, 20 m Self-Paced Walk Test, 5 Times Sit-to-Stand Test and Grip Strength measured with a Jamar Dynamometer were used to quantitate changes in cognition, depression, fatigue and neurological function after a single 25 mg perispinal etanercept dose in a patient with severe long COVID of 12 months duration. Results: Following perispinal etanercept administration there was immediate neurological improvement. At 24 h, there were remarkable reductions in chronic post-COVID-19 fatigue and depression, and significant measurable improvements in cognition, executive function, phonemic verbal fluency, balance, gait, upper limb coordination and grip strength. Cognition, depression and fatigue were examined at 29 days; each remained substantially improved. Conclusion: Perispinal etanercept is a promising treatment for the chronic neurologic dysfunction that may persist after resolution of acute COVID-19, including chronic cognitive dysfunction, fatigue, and depression. These results suggest that long COVID brain neuroinflammation is a potentially reversible pathology and viable treatment target. In view of the increasing unmet medical need, clinical trials of perispinal etanercept for long COVID are urgently necessary. The robust results of the present case suggest that perispinal etanercept clinical trials studying long COVID populations with severe fatigue, depression and cognitive dysfunction may have improved ability to detect a treatment effect. Positron emission tomographic methods that image brain microglial activation and measurements of cerebrospinal fluid proinflammatory cytokines may be useful for patient selection and correlation with treatment effects, as well as provide insight into the underlying pathophysiology.